Assessment of the usefulness for learning of the flipped classroom model - Naranjo Iturralde, Carlos Héctor (Scientific journal of social studies, 2023)
The need to adapt to the new conditions required by online education led us to implement the flipped classroom methodology using new didactic resources. The research aims to evaluate the usefulness of didactic resources for student learning in the non-face-to-face course of Business Economic Seminars at the American University (UAM) in the August-December 2021 semester. The study was developed using a quantitative approach with a descriptive scope and an experimental design with a sample of 28 students. The instrument used was a five-point Likert scale with 10 items. The statistic was determined to fall within the region, making the null hypothesis true. Therefore, it is affirmed that the content, applications, and learning activities used in the Business Economic Seminars course are useful for student learning, and this is generalizable to the universe.
Keywords: Autonomous learning; active education; flipped classroom; didactics; information and communication technologies